Giant Serpentine Aneurysm of the Middle Cerebral Artery - Lee, Seung Joo (The Korean Neurosurgical Society, 2010)
Giant serpentine aneurysms are rare and have distinct angiographic findings. The rarity, large size, complex anatomy and hemodynamic characteristics of giant serpentine aneurysms make treatment difficult. We report a case of a giant serpentine aneurysm of the right middle cerebral artery (MCA) that presented as headache. Treatment involved a superficial temporal artery (STA)-MCA bypass followed by aneurysm resection. The patient was discharged without neurological deficits, and early and late follow-up angiography disclosed successful removal of the aneurysm and a patent bypass graft. We conclude that STA-MCA bypass and aneurysm excision is a successful treatment method for a giant serpentine aneurysm.